Morbimortalidad Anestésica en el Centro Médico Naval. Enero 1995 - Diciembre 1997 - Meneses Román, Elva (1999)
OBJECTIVES: To determine the type and incidence of anaesthetic procedure related complications according to the patients characteristics. MATERIAL AND METHODS: A retrospective, descriptive study, between January 1995 and December 1997, evaluating clinical records from 9 568 patients who underwent surgery, was made. Intraoperatory complications, age, gender, ASA(American Society Anesthesiology) index, cardiovascular surgical risk index, anaesthetic medication used, anaesthetic stage in which the event occurs, priority level of surgery, and kind of surgery were considered. We reviewed the anaesthetic record of each patient. RESULTS: The frequency of intraoperatory complications was 4,32% within the study period. Hypotension (28,78%), arrhytmias (22,54%), hypertension (11,99%) and unexpected general anaesthesia (11,27%) were the most frequent complications. CONCLUSIONS: During the study period, there was a lower anaesthetic procedure-related morbimortality at the Centro Médico Naval.